Print Legal Regulations on Preventive Policies in Handling Narcotics Crimes - Sibarani, Henri Ritson; Ramadhan, M. Citra; Zulyadi, Rizkan (Journal of Public Representative and Society Provision, 2025)
Drug abuse is a serious problem that has a negative impact on individuals, families, and society. Combating drug crimes in Indonesia requires not only a repressive approach, but also effective preventive policies based on the rule of law. This study aims to analyze the legal rules underlying preventive policies in combating drug crimes, with a focus on the effectiveness of implementation and the obstacles faced in the field. This study uses a normative legal method, which analyzes laws and regulations such as Law Number 35 of 2009 concerning Narcotics, Regulation of the Chief of Police No. 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice, and Attorney General’s Guidelines No. 18 of 2021 concerning Settlement of Narcotics Crime Cases Through Rehabilitation. The results of the study indicate that preventive policies have an important role in preventing drug abuse, especially through education, socialization, and cross-sectoral cooperation. However, the implementation of this policy is often hampered by weak coordination between institutions, limited resources, and low public awareness. Therefore, preventive policies supported by strong legal regulations and effective implementation can be a significant strategy in overcoming drug crimes. This study recommends the need for evaluation and improvement of regulations, increasing the capacity of implementers in the field, and strengthening community participation to create a safer environment free from the threat of drugs.